Women warriors in Southeast Asia - Lanzona, Vina A.; Rettig, Tobias (Routledge studies in the modern history of Asia, 2020)
"This book brings together a wide range of case studies to explore the experiences and significance of women warriors in Southeast Asian history from ancient to contemporary times. Using a number of sources, including royal chronicles, diaries, memoirs and interviews, the book discusses why women warriors were active in a domain traditionally preserved for men, and how they arguably transgressed peacetime gender boundaries as agents of violence. From multidisciplinary perspectives, the chapters assess what drove women to take on a variety of roles, namely palace guards, guerrillas and war leaders, and to what extent their experiences were different to those of men. The reader is taken on an almost 1,500-year long journey through a crossroads region well-known for the diversity of its peoples and cultures, but also their ability to creatively graft foreign ideas onto existing ones. The book also explores the re-integration of women into post-conflict Southeast Asian societies, including the impact (or lack thereof) of newly established international norms, and frequent turn towards pre-conflict gender roles in these societies. Written by an international team of scholars, this book will be of interest to academics working on Southeast Asian Studies, Gender Studies, low intensity conflicts and revolutions, and War, Conflict, and Peace Studies"--